2011
DOI: 10.1007/s13197-011-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life and colour change kinetics of Aloe vera gel powder under accelerated storage in three different packaging materials

Abstract: Aloe vera gel powder was produced through dehumidified air drying of Aloe vere gel at optimized conditions of temperature, relative humidity and air velocity of 64°C, 18% and 0.8 m.s −1 , respectively. The powder was packed in three different packaging materials viz., laminated aluminum foil (AF), biaxially oriented polypropylene (BOPP) and polypropylene (PP). The shelf-life of the powder was predicted on the basis of free flowness of product under accelerated storage condition (38±1°C, 90± 1% relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
2
25
0
2
Order By: Relevance
“…Statistical analysis showed that moisture content of SDBC powder during the storage time was significantly affected by packaging materials, storage conditions and storage time (Table 1). which was consistent with the results obtained by Kumar and Mishra (2004), Ramachandra and Rao (2011) and Agrahar-Murugkar and Jha (2011). The variation of water activity and the T-T g (the difference between storage temperature and T g ) of SDBC powders as a function of storage time was predicted by using water adsorption isotherms and the state diagram, respectively, and presented in Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Statistical analysis showed that moisture content of SDBC powder during the storage time was significantly affected by packaging materials, storage conditions and storage time (Table 1). which was consistent with the results obtained by Kumar and Mishra (2004), Ramachandra and Rao (2011) and Agrahar-Murugkar and Jha (2011). The variation of water activity and the T-T g (the difference between storage temperature and T g ) of SDBC powders as a function of storage time was predicted by using water adsorption isotherms and the state diagram, respectively, and presented in Fig.…”
Section: Resultssupporting
confidence: 93%
“…The final moisture content was decided based on the free flowability of the powder and its water activity. This moisture content was considered as critical moisture content and the corresponding water activity was calculated using the GAB parameters (Ramachandra and Rao 2011). According to the preliminary results, the estimated GAB parameters M m , C and K at 25°C were 3.983 % dry basis, 39.804 and 0.957, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They also found case hardening effect in the samples dried at 70 °C. The influence of drying process on rehydration [10] , structural properties [11] , color and shelf life [12,13] , physicochemical and antioxidant capacity [14] of aloe vera have been reported earlier. Vega-Gálvez et al [15] studied the rehydration characteristics of aloe vera as a function of temperature, and they found that drying process caused irreversible modification in the cell structure of the aloe vera gel.…”
mentioning
confidence: 64%
“…Dehumidified air drying has been used in the manufacturing industries, as an alternative to conventional drying technologies, and it has other benefits such as environmental friendliness, cost effectiveness and handling sensible and latent heat loads independently. Dehumidified air drying has been studied for different plant based products such as aloe vera [12] , apple [18] and ginger [19] .…”
mentioning
confidence: 99%
“…After storage of 40 days at 38 ± 1°C, 33 per cent RH there was greater colour change in PL powder packaged in MP than in ALP and this value correlated well with the Browning index values explained in previous section. The colour change of aloe vera powder during storage followed first order reaction kinetics with K value of 0.0444 per day for AF, 0.075 per day for BOPP and 0.0498 per day for PP 12 . Dehydrated paprika samples at degraded significantly rapidly at high temperature and RH, compared to samples room temperature storage.…”
Section: Changes In Colour During Storagementioning
confidence: 97%